2020
DOI: 10.1097/qai.0000000000002460
|View full text |Cite
|
Sign up to set email alerts
|

Lower Cumulative Antiretroviral Exposure in People Living With HIV and Diabetes Mellitus

Abstract: Objective: People living with HIV (PLWH) are living longer and developing more non-AIDS comorbidities, which negatively impact antiretroviral therapy (ART) adherence. Tenofovir diphosphate (TFV-DP) in dried blood spots (DBS) is a novel pharmacologic measure of cumulative ART adherence that is predictive of viral suppression and future viremia. However, the relationship between non-AIDS comorbidities and this adherence measure is unknown. We aimed to evaluate the association between 3 non-AIDS comor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 43 publications
0
7
0
1
Order By: Relevance
“…Second, a more complex medication regimen has the potential for more drug‐drug interactions, which could theoretically impact TFV‐DP concentrations; however, interactions of this magnitude are not likely 34,35 . Third, a more complex medication regimen is a marker for more comorbidities, which could influence drug concentrations, as was previously observed in this cohort in PWH and diabetes mellitus 36 . Finally, patients who are nonadherent to ART may be more likely to require prophylactic medications for opportunistic infections, which in turn would increase the pMRCI.…”
Section: Discussionmentioning
confidence: 69%
“…Second, a more complex medication regimen has the potential for more drug‐drug interactions, which could theoretically impact TFV‐DP concentrations; however, interactions of this magnitude are not likely 34,35 . Third, a more complex medication regimen is a marker for more comorbidities, which could influence drug concentrations, as was previously observed in this cohort in PWH and diabetes mellitus 36 . Finally, patients who are nonadherent to ART may be more likely to require prophylactic medications for opportunistic infections, which in turn would increase the pMRCI.…”
Section: Discussionmentioning
confidence: 69%
“…Tenofovir disoproxil fumarate (TDF) is commonly used for pre-exposure prophylaxis alone or in combination with other antiretroviral drugs as post-exposure prophylaxis [46,47]. Despite TDF's low CNS-penetration rate, studies have reported its neurotoxic effect and diabetic and neurocognitive implications [11,12,19]. Silver nanoparticles have been shown to cross the blood-brain barrier independent of dosage and route of administration [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a 25% reduction in the TDF concentration was observed in dried blood spots of people with diabetes mellitus compared with non-diabetic control adults [12]. Long-term administration of NRTIs, especially TDF, is associated with metabolic disorders, diabetes mellitus, and systemic and organ toxicity [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations